2014
DOI: 10.1111/and.12264
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofCissampelos capensisrhizome extract on human spermatozoain vitro

Abstract: SummaryCissampelos capensis is commonly known by the Afrikaans name 'dawidjies' or 'dawidjieswortel'. C. capensis is the most important and best-known medicinal plant of the family Menispermaceae used by the Khoisan and other rural people in the western regions of South Africa. Among numerous other ailments, it is traditionally taken to treat male fertility problems. Yet, no studies have investigated the effects of this plant or its extracts on human spermatozoa. The aim of study was to investigate the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…A previous study reported that the administration of alkaloids and triterpenoids has a negative effect on fertility [ 36 ], as they can inhibit spermatogenesis [ 37 ] and alter the morphology and histology of testes [ 38 ]. These results are comparable with a study that administered Cissampelos capensis rhizomes , which caused a dose-dependent increase in sperm intrinsic superoxide production leading to sperm capacitation and DNA fragmentation [ 39 ]. A similar study using withanolide-A also reported a decrease in the testosterone levels in rats, which reduced fertility and inhibited spermatogenesis [ 40 ].…”
Section: Discussionsupporting
confidence: 87%
“…A previous study reported that the administration of alkaloids and triterpenoids has a negative effect on fertility [ 36 ], as they can inhibit spermatogenesis [ 37 ] and alter the morphology and histology of testes [ 38 ]. These results are comparable with a study that administered Cissampelos capensis rhizomes , which caused a dose-dependent increase in sperm intrinsic superoxide production leading to sperm capacitation and DNA fragmentation [ 39 ]. A similar study using withanolide-A also reported a decrease in the testosterone levels in rats, which reduced fertility and inhibited spermatogenesis [ 40 ].…”
Section: Discussionsupporting
confidence: 87%
“…Leaves, rhizome and roots (Wet and Wyk, 2008;van de Venter et al, 2008) Diuretic Rhizome (Wet et al, 2011;Shalaweh et al, 2015b) Emetic…”
Section: ) Blood Puri Icationmentioning
confidence: 99%
“…The extract resulted in a dose-dependent increase in ROS, DNA fragmentation, capacitated and hyper activated spermatozoa (Shalaweh et al, 2015a). Similarly, (Shalaweh et al, 2015b) evaluated the spermatozoa activities of methanol fractions of C. capensis by assessing sperm motility, ROS, DNA-fragmentation, acrosome reaction and capacitation. The extract resulted in higher values for ROS, capacitation and hyperactivation (Shalaweh et al, 2015b).…”
Section: Antifungal Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The antioxidants present in plant products help in the stimulation of cellular defense system and biological system against oxidative damage [4]. In South Africa, medicinal plants are used to treat and manage various ailments such diabetes, hypertension, diarrhea, and male reproductive disorders [5,6]. Approximately 3000 plant species from more than 30,000 higher plant species are used in traditional medicines for the treatment of various conditions [7].…”
Section: Introductionmentioning
confidence: 99%